Artful climate change communication: overcoming abstractions, insensibilities, and distances. (11th July 2017) - Hawkins, Harriet; Kanngieser, Anja
Abstract : This article considers how visual and sonic art creates encounters through which audiences can experience climate change. Building on reviews published in WIREs Climate Change on images, films, drama, climate science fiction, and other literary forms, we examine how audio and visual art addresses the enduring problems of climate change communication. We begin with three of these problems: climate change's often abstract nature, the distances in time and space between those who cause climate change and the places its effects are felt, and forms of human–environmental relations that shape how climate is understood. We reflect on how, through a combination of vision and sound, art creates sensory experiences that tackle these challenges. In querying how our artistic examples bring about environmental engagements, we combine an analysis of the representations and narratives of these works with an appreciation of their aesthetic form—in short, how these art pieces activate emotional and experiential responses. While we recognize the limits of what art can do, especially the gallery‐based forms of work we study here, we argue that spending time exploring the encounters that art creates helps us to understand what it brings to the communication of climate change. It also demonstrates how lessons learnt about sensory experience, affect, and emotions might be more widely applied to the analysis of cultural forms—from literature to films—and their role in climate change communication. WIREs Clim Change 2017, 8:e472. doi: 10.1002/wcc.472 This article is categorized under: Trans‐Disciplinary Perspectives > Humanities and the Creative Arts Abstract : A paper exploring how audio‐visual art might help tackle some of the challenges of communicating climate change.